2016
DOI: 10.3892/mmr.2016.5416
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of TGF-β1 enhance human umbilical cord-derived mesenchymal stem cell fibronectin production and extend survival time in a rat model of lipopolysaccharide-induced acute lung injury

Abstract: Abstract. Mesenchymal stem cells (MSCs) are an attractive cellular source for cell-based therapy, tissue engineering and regenerative medicine. However, the use of MSCs is limited by their low incorporation rate in the graft environment. The majority of cells are lost from the graft within 1 month, due to reduced microenvironment or local inflammation at the graft site. The extracellular matrix (ECM) may assist the survival and expansion of MSCs. The present study aimed to identify an effective approach to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 46 publications
1
42
2
Order By: Relevance
“…UC-MSC primed with TGF-β1 displayed increased proliferation and marked upregulation of extracellular matrix genes, notably fibronectin. TGF-β1-primed MSC survived longer in damaged lungs and reduced the severity of lipopolysaccharide-induced lung injury [ 54 ]. Additionally, some studies have demonstrated that TGF-β1 is capable of inducing the mobilization and migration of BM-MSC to bone remodeling.…”
Section: Msc Priming With Cytokinesmentioning
confidence: 99%
“…UC-MSC primed with TGF-β1 displayed increased proliferation and marked upregulation of extracellular matrix genes, notably fibronectin. TGF-β1-primed MSC survived longer in damaged lungs and reduced the severity of lipopolysaccharide-induced lung injury [ 54 ]. Additionally, some studies have demonstrated that TGF-β1 is capable of inducing the mobilization and migration of BM-MSC to bone remodeling.…”
Section: Msc Priming With Cytokinesmentioning
confidence: 99%
“…Nonhuman primate studies demonstrated that 7 days after infusion of allogeneic or autologous MSCs, only a minor fraction of the cells (less than 3%) engraft in different tissues (21); the majority of these cells were found in the kidney, lung, thymus, and skin (22). Recent findings showed that a very low concentration of MSCs was identified in vivo after 4 weeks (23).…”
Section: Discussionmentioning
confidence: 99%
“…The other methodologies are using the extracorporeal organ replacement for acute renal failure or fulminant acute liver failure, skeletal stem cell implantation for bone regeneration, which are already under clinical application [33,34]. As the considerable amount of evidence has been obtained from basic research and its translation towards the clinical research, MSCs placed in medical practice as an alternative treatment option as safe and effective cellbased therapies for immune-mediated inflammatory diseases such as graft versus-host disease (GVHD) and systemic lupus erythematosus (SLE) [34][35][36][37].…”
Section: Stem Cells As An Option Curing Sars-cov Induced Pulmonary Immentioning
confidence: 99%
“…One suggested function of stem cells is their ability to regulate the inflammatory response and promote tissue repair and regeneration. MSCs have been demonstrated to improve organ functions in cardiovascular, renal, hepatic, and multiple other disorders [34][35][36][37].…”
Section: Stem Cells As An Option Curing Sars-cov Induced Pulmonary Immentioning
confidence: 99%